THE CORPOREITY OF THE CHILDREN IN THE SCHOOL: CHALLENGES TO THINK THE FORMATION (Fiep Bulletin - online, 2011)
In this article we do a reflection on the corporeity in the school, inquire: How the school, through the systematic education, has been building a corporeity (gestures, movements, rhythms, thoughts, etc.)? Which corporeity do the children build and / or express through jokes and plays? How will the corporeity built and expressed in the jokes and plays of the children be able to contribute to the transformation of the school? We use a qualitative methodology, we were registering the daily life, the marks written in the walls, in the existent documents in the school, old photographies prospected in the trunks of the oblivion, talked with children of a 1st series. The register and the systematic analysis showed us that these convey values and experiences opposed to that of the school practices. In the school, the teachers, the teachers prepare standards for the children, whom they themselves do not carry out - as it was the case of the standard for the delays; in the jokes and plays, the standards were combined between the participants, in the beginning, and they were valid for all. In the school, the numbered classrooms reveal like the identity of each one of the pupils and pupils - the name - it gives place to the number, reference to the individuals who make part of an influenced society; the fun of hide-and-seek, on the contrary, emphasizes the importance of each one so that the activity and the life have continuity and if it carries out.
Keywords: Corporeity; infancies; school